Resident-Managed Elder Intentional Neighborhoods: Do They Promote Social Resources for Older Adults?. Issue 7 (16th November 2016) - Glass, Anne P.
ABSTRACT: Social isolation has serious negative public health impacts for older adults. Survey data were collected at three resident-managed elder intentional neighborhoods in the United States ( n = 59), to determine if these neighborhoods, each based on the cohousing model, promote development of social resources for their residents. Social resources were measured on three dimensions: social networks, neighborly support, and satisfaction with the neighborhood community. Respondents were White, mean age of 73.3 (range = 63–91), primarily female (76.3%), and generally had high levels of education and self-reported health. Almost half (47%) were never married/divorced and 37% were childless. Inclusion of neighborhood ties ameliorated risk of social isolation. Satisfaction with support and a variety of neighboring behaviors were reported. These neighborhoods are meeting the needs of a potentially at-risk population as an avenue to promote social resources and reduce social isolation. The implications for gerontological social workers include a role in helping to mobilize and support these types of neighborhoods as a way to encourage mutual support among older adults. With the increase in the aging population, such models of proactive interdependence and communal coping have the potential to lessen or delay the demands that socially isolated elders place on social workers.